Comparative Study of Modulation Techniques for Two-Level Voltage Source Inverters - Barry W. Williams; Peng Li; Grain Adam; Derrick Holliday (Renewable Energy and Sustainable Development)
A detailed comparative study of modulation techniques for single and three phase dc-ac inverters is presented.  Sinusoidal Pulse Width Modulation, Triplen Sinusoidal Pulse Width Modulation, Space Vector Modulation, Selective Harmonic Elimination and Wavelet Modulation are assessed and compared in terms of maximum fundamental output, harmonic performance, switching losses and operational mode.  The presented modulation techniques are applied to single and three phase voltage source inverters and are simulated using SIMULINK.  The simulation results clarify the inverter performance achieved using the different modulations techniques.